JQuery in action - Bibeault, Bear (Manning, 2008)
"JQuery is a fast-paced introduction and guide. It shows you how to traverse HTML documents, handle events, perform animations, and add Ajax to your Web pages. The book's unique "lab pages" anchor the explanation of each new concept in a practical example. You'll learn how jQuery interacts with other tools and frameworks and how to build jQuery plugins. This book requires a modest knowledge of JavaScript and Ajax."--Jacket